English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-21 12:41:23 · 5 answers · asked by Phillip V 1 in Science & Mathematics Mathematics

5 answers

3x^2+x-2=(3x-2)(x+1) so the roots are 2/3, -1.

2007-01-21 12:45:07 · answer #1 · answered by XelaleX 2 · 0 0

First, rewrite the equation:
3x^2 + x - 2 = 0
and then use the quadratic formula

roots = (-b+- sqrt(b^2-4ac))/2a
where a = 3, b = 1, and c = -2

2007-01-21 20:45:53 · answer #2 · answered by firefly 6 · 0 0

Rewrite the equation to 3X^2-2+X=0 then factor to get the answer

2007-01-21 20:49:14 · answer #3 · answered by Ferret 4 · 0 0

(1, -2/3)

2007-01-21 20:52:11 · answer #4 · answered by Anonymous · 0 0

3x^2+x-2=0
(3x-2)(x+1)=0
x=-1, 2/3

2007-01-21 20:45:12 · answer #5 · answered by VanessaM 3 · 0 0

fedest.com, questions and answers